Pengaruh Kepemimpinan Islami dan Kinerja Pemerintah Daerah terhadap Pembangunan Ekonomi di Kota Tangerang Selatan dengan Pendekatan HAHSLM - Engkur Engkur; Roikhan Maziz; Doni Wiratmoko (Jurnal Ekonomi, 2018)
South Tangerang City is currently experiencing progress and development after the regional division. Of course, all of that did not escape the leadership of the regional head. This study aims to analyze the influence of regional head Islamic leadership and local government performance on economic development in the city of South Tangerang. The data used in this study is primary data obtained from questionnaires distributed to the people of South Tangerang city. The data analysis method used is the Partial Least Square (PLS) method with SmartPLS 2.0 software and Microsoft Excel 2010. The results of this study indicate that the Islamic leadership variable has a significant effect on economic development in South Tangerang City, with a significance value of 0.000 which is smaller than the significance value. used is 0.05. The Islamic leadership variable also has a significant effect on the accountability of local government performance in South Tangerang City. While the local government performance accountability variable has no significant effect on economic development in South Tangerang City with a t-statistic value of 1.063 which is smaller than the t-table of 1.96 and a significance value of 0.288 greater than the significance used, which is 0.05.